Surgically confirmed cases for human Hydatidosis in Thi-Qar province - حبش عواد عبد الحسين; جاسم حنش وسام (University of Thi-Qar Journal of Science, 2016)
The present study was conducted to evaluate number of recorded cases with human hydatidosis and prevalence of disease. Fifty eight patients were diagnosed with hydatidosis in different organs such as liver, lung, kidney and spleen and treated surgically at Al-Hussein Imam Teaching hospital in Nassiriyah city center of Thi-Qar province during 2015.Seventy two hydatid cyst was recorded with 1.24 intensity of infection. The present study showed the hydatidosis infect female 67.24 % more than male 36.76 %. The age group 21 – 30 years and 31 – 40 years showed highest of infection percentage 24.14 % and 20.69 % respectively. The right lobe of liver was most affected with infection 58.62 % and too infections recorded in right lung 8.62 %, left lung 10.34 % and left kidney 1.72 %. The study showed total rate of fertile hydatid cysts 81.82 % and sterile hydatid cysts 18.18 %. Housewives recorded highest of infection 87.18 % than others.